Market Perspective Determinants for Stock Returns in Manufacturing Companies on the IDX - Widianingtyas, Rifa Pramesti; Irawati, Zulfa (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
he purpose of this study was to analyze the effect of Economic Value Added (EVA), Price toBook Value (PBV), Earning Per Share (EPS) on stock returns. This study uses a quantitativedescriptive method. The data sources used are secondary data sources, in the form offinancial report data from food and beverage manufacturing sector companies listed on theIndonesia Stock Exchange from 2019-2021 and annual reports. The object of this researchis a food and beverage manufacturing company that is listed on the IDX in 2019-2021. Theanalytical method used is descriptive statistical analysis, classic assumption test, namely:normality test, multicollinearity test, autocorrelation test and heteroscedasticity test andmultiple linear regression analysis. Then do the t test and F test. Data collection techniquesusing purposive sampling method. The results in this study partially, Economic ValueAdded (EVA) and Earning Per Share (EPS) have a positive and significant effect on stockreturns. While simultaneously Economic Value Added (EVA), Price to Book Value (PBV) andEarning Per Share (EPS) together influence stock returns.